Synchrotron X-Ray diffraction analysis of cyclic deformation behaviour of thin gold films. (12th July 2011) - Eve, S.; Thuault, A.; Hofmann, F.; Korsunsky, A.M.
Innovative micro-optical sensors involve metallic thin films deposited on polymer substrates. In the present study, we investigate in detail the state of macroscopic and microscopic stress that exists within thin gold films on polycarbonate substrate after deposition, and the evolution of these stresses during reversed in situ tensile testing and as a consequence of fatigue cycling.